Immunohistochemical assessment of the MIB, CK-14, p63, p16, Cal A, and Cys A markers in spindle cell squamous cell carcinomas of the lip (Revista da Faculdade de Odontologia - UPF, 2013)
Objective: with the objective of testing the expression of the protein markers MIB, CK14, p63, p16, Cal A, and Cys A in the pathogenesis of oral spindle cell carcinoma, we conducted an immunohistochemical study of the expression of the protein markers MIB, CK14, p63, p16, Cal A, and Cys A in human biopsy specimens of these lesions. Methods: fifteen histological specimens of spindle cell squamous cell carcinoma of the lower lip were obtained from the Department of Oral Pathology, Bahia Federal University. Immunohistochemical analyses were performed at the Molecular Biology Laboratory of the Department of Otorhinolaryngology, Heidelberg University, Germany. Results: statistical analysis revealed no association between markers. There was strong positive staining for Ck14, MIB, and Cal A in 93.3% of cases, thus establishing a strong association. Conclusion: p63, p16, MIB, Cal A, Cys A are markedly expressed and p16 is strongly suppressed in oral cavity tumors, which suggests that the latter protein may play a role in negative regulation of cell cycle progression.